Evaluating Websites of Conservation Labs in Museums using Fuzzy Multi-Criteria Decision Making theories - Kabassi, Katerina; Botonis, Athanasios; Karydis, Christos (Informatica, 2020)
The museums’ conservation labs and the treatments on the artefacts, many times are overlooked and are not obvious for the public. Nevertheless, their content may be of interest to students, researchers, archaeologists, tourists, artists for further education and preservation guidelines purposes. In this paper we evaluate the electronic presence of museums’ conservation labs using both empirical and inspection methods of evaluation. For this purpose, a combination of Analytic Hierarchy Process (AHP) and Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is used to implement an evaluation experiment that combines inspection and empirical methods of evaluation. The proposed scheme of evaluation that implements a combination of methods and decision making theories has been used for evaluating the 29 websites of museum’s conservation labs and ranks them taking into account their content, usability and functionality.